Target capture data resolve recalcitrant relationships in the coffee family (Rubioideae, Rubiaceae) - Olle Thureborn; Sylvain G. Razafimandimbison; Niklas Wikström; Niklas Wikström; Catarina Rydin; Catarina Rydin (Frontiers in Plant Science, 2022)
Subfamily Rubioideae is the largest of the main lineages in the coffee family (Rubiaceae), with over 8,000 species and 29 tribes. Phylogenetic relationships among tribes and other major clades within this group of plants are still only partly resolved despite considerable efforts. While previous studies have mainly utilized data from the organellar genomes and nuclear ribosomal DNA, we here use a large number of low-copy nuclear genes obtained via a target capture approach to infer phylogenetic relationships within Rubioideae. We included 101 Rubioideae species representing all but two (the monogeneric tribes Foonchewieae and Aitchinsonieae) of the currently recognized tribes, and all but one non-monogeneric tribe were represented by more than one genus. Using data from the 353 genes targeted with the universal Angiosperms353 probe set we investigated the impact of data type, analytical approach, and potential paralogs on phylogenetic reconstruction. We inferred a robust phylogenetic hypothesis of Rubioideae with the vast majority (or all) nodes being highly supported across all analyses and datasets and few incongruences between the inferred topologies. The results were similar to those of previous studies but novel relationships were also identified. We found that supercontigs [coding sequence (CDS) + non-coding sequence] clearly outperformed CDS data in levels of support and gene tree congruence. The full datasets (353 genes) outperformed the datasets with potentially paralogous genes removed (186 genes) in levels of support but increased gene tree incongruence slightly. The pattern of gene tree conflict at short internal branches were often consistent with high levels of incomplete lineage sorting (ILS) due to rapid speciation in the group. While concatenation- and coalescence-based trees mainly agreed, the observed phylogenetic discordance between the two approaches may be best explained by their differences in accounting for ILS. The use of target capture data greatly improved our confidence and understanding of the Rubioideae phylogeny, highlighted by the increased support for previously uncertain relationships and the increased possibility to explore sources of underlying phylogenetic discordance.